The Amazing Journey of Reason (2020)
This Open Access book explores questions such as why and how did the first biological cells appear? And then complex organisms, brains, societies and –now– connected human societies? Physicists have good models for describing the evolution of the universe since the Big Bang, but can we apply the same concepts to the evolution of aggregated matter –living matter included? The Amazing Journey analyzes the latest results in chemistry, biology, neuroscience, anthropology and sociology under the light of the evolution of intelligence, seen as the ability of processing information. The main strength of this book is using just two concepts used in physics –information and energy– to explain: The emergence and evolution of life: procaryotes, eukaryotes and complex organisms The emergence and evolution of the brain The emergence and evolution of societies (human and not) Possible evolution of our "internet society" and the role that Artificial Intelligence is playing